Prediction of Prospective Anti-Parkinson Phytochemicals using Prediction of Activity Spectra of Substances Software to Justify 3R’s Ethics of In Vivo Evaluation (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Parkinson’s disease (PD) is a chronic progressive devastative disorder of neurons characterized bya muscle rigidity, tremors, bradykinesia etc. In present scenario, it is affecting more than 1% population above 50years of age and hence is an important concern in society. Advancement in research field in recent decades hasled to upsurge the use of animals for evaluation of new drugs. Objective: In contemplation of upward trend inuse of animals, PASS (prediction of activity spectra of substances), a web tool, provides an informative predictiondata for different pharmacological activity of compounds without using the animals which justifies the 3R’sethics (Reduction, Replacement, and refinement) to be followed for in vivo evaluation. Methods: For predictionof pharmacological activities of anti-parkinson compounds, canonical smiles of phytochemicals were obtainedfrom Pubmed and used in the software for prediction of relevant pharmacological activity so that phytochemicals,showing best results can be further explored for in vivo evaluation against PD. Using PASS online software,biological activity spectra for nine different activities related to Parkinson’s disease for selected phytochemicalswas predicted and compared with marketed compounds. Result: Out of selected phytochemicals, scopolamineand atropine have shown highest antiparkinsonian activities. Piperine was also found to have antiparkinsonianactivity. Elaeocarpine, harmine and oxyresveratrol have found to have comparable activity for this condition.Conclusion: This article describes the utility of PASS to justify the 3R’s concept which is to be followed for thefurther in vivo exploration of compounds.